The Southern African Food Security Crisis, Causes and Responses - (:unkn) unknown (My University, 2003)
Over the last few decades, Southern African governments have identified the eradication or alleviation of poverty as a key objective of developmental programmes. In spite of these repeated articulations and ongoing efforts poverty levels have not fallen. In fact, poverty has gradually worsened culminating in the present region-wide food crisis. The crisis will affect over 15 million people through impacts ranging from lack of access to food, food insecurity, malnutrition, and possibly famine. The ongoing food crisis has had a significant toll and brought great suffering to many in the region. However, within the spectre of starvation and collapse lie opportunities for key players in the region, both governmental and non-governmental, to identify and address the factors underlying the vulnerability that has allowed the prevailing crisis to develop. This treatise aims to give an overview of the factors underlying this crisis, some of the key responses to it, the lessons that have been learnt from it to date and the opportunities for intervention.
Keywords: African Research